Experience of professional management of orthopedic nursing workers (骨科护工专业化管理体会) - ZHANG Pin (张聘); CHEN Jinling (陈金铃); Liu Jie (刘洁) (中西医结合护理)
This paper summarized the experience of professional management of orthopedic nursing workers, including personnel selection, determination of job responsibilities, training, assessment and daily monitoring. The professional management provide a . for orthopedic nursing workers can The professional management is critical to the advancement of specialized skills in nursing workers. It is helpful for improving cooperation between nurses and nursing works and therefore ensuring the safety and satisfaction of patients. (本文总结骨科护工专业化管理的相关经验, 包括人员选择、明确工作职责、培训及考核、日常监督等。通过专业化的管理, 提升护工专业化技能, 有助于其更好地协助护士工作, 保证患者安全, 提升患者满意度。)